Detection of Ureteral Stump Transitional Cell Carcinoma, Presenting as Bone Metastases from Unknown Primary by 18F-FDG PET/CT: A Case Report with Review of Literature - Nikolova, Petya N.; Hadzhiyska, Valeria H.; Mladenov, Kiril B.; Ilcheva, Mihaela G.; Veneva, Stefani; Dineva, Svetla E.; Mladenov, Boris S. (Indian Journal of Radiology and Imaging, 2021)
A case of occult carcinoma of the ureteral stump is reported. A 67-year-old man presented with pain syndrome due to multiple bone metastases from unknown primary origin detected by previous imaging studies as magnetic resonance imaging, whole body contrast-enhanced computed tomography (CT), and technetium-99m methyldiphosphonate bone scan. He had undergone a right nephrectomy for a benign disease previously. He was referred to our department for an 18F-fluoro-2-deoxy-D-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) to help localize possible primary tumor. Our observations in this case show that the use of 18F-FDG PET/CT successfully and more accurately evaluated the overall tumor burden and led to a rapid decision of an adequate therapeutic approach.
Keywords: 18F-FDG PET/CT; bone metastases; cancer of unknown primary; ureteral stump